ANALYSIS ON THE INFLUENCE OF DUCT CASING GEOMETRY ON THE PERFORMANCE OF A DUCTED FAN - Pangaribuan, Marcellino; Hartono, Firman (Mesin, 2024)
This paper aims to evaluate the influence of an electric ducted fan’s (EDF) geometry on its performance through parameter correlation analysis. Sample data was first built by generating new EDF models with varying duct casing geometries through optimal space-filling (OSF) sampling method. Afterwards, each model was numerically solved with computational fluid dynamics (CFD) analysis to obtain each model’s thrust, required power, and efficiency. It is found that the casing’s inlet lip diameter displays the greatest influence on the EDF’s total thrust, as the inlet diameter determines the casing’s surface area affected by the low-pressure region ahead of the rotating fan blades. Additionally, it is found that length of the casing’s exhaust lip affects the EDF’s efficiency, while the exhaust lip diameter displays the highest correlation with the fan’s required power.